Dr. Alexandra Belkind: Pathmaker in Women’s Health in the Holy Land/Land of Israel 1905-1912 - Shvarts, Shifra; Shehory-Rubin, Zipora; Romem, Pnina; Romem, Yitzhak (DELTOS, 2025)
In 1906, a women’s clinic was established in Jaffa- the first of its kind in the Holy Land / Land of Israel under Ottoman rule. The establishment of this clinic, which operated between 1906-1914 was revolutionary, serving as a catalyst for change in societal attitudes towards women’s health, particularly within the Muslim community. During the operation of her women’s clinic, Dr. Belkind treated approximately one thousand women whom she diagnosed and/or treated for female-specific conditions (gynaecology, maternity and mental health) alongside general medical concerns such as influenza and various inflammatory disorders. The clinic provided medical care on a non-sectarian basis without discrimination on racial or religious grounds, and over half of her patients were Muslims, while the remainder were equally divided between Jewish and Christian women. The clinic’s patient files constitute a unique primary source of information documentingbhow women’s health issues were viewed and addressed at the start of the 20th century in the Holy Land / Land of Israel under Ottoman administration. In her medical reports, Dr. Belkin addressed in particular issues such as sexual relationships, abortion, domestic violence as well as malnutrition, and high infant mortality and suicide among women. She provides details on the impact of forced adolescent marriage on women’s health and the link between child marriages and secondary infertility, psychological problems and stillbirths. As a compassionate listener, Dr. Belkind, recorded their complaints in her files, noting in detail the psychosocial significance of the contents of her conversations. The study, based on Dr. Belkind’s medical files on female patients she treated in this area between 1906-1914, provides valuable insights regarding the specific health problems faced by Muslim women in particular in the early 20th century in the Land of Israel and into the complex interface between Western medicine and women from a traditional society.